تکنولوجیا المکتبات الذکیة ودورها فى دعم اقامة المدن الذکیة : دراسة حالة لمکتبة الملک عبد العزیز العامة بمدینة الریاض - د. على عبد المحسن على (المجلة الدولية لعلوم المكتبات والمعلومات)
The study aims to "identify the technology of smart libraries used in theKing Abdulaziz Public Library in Riyadh and the role it can be played insupporting the initiative of the city of Riyadh "smart city "The study has used "Case study method ", and the researcher relied ondata collection on check list and personal observation through frequent visits tothe library branches and personal interviews with the librarians of the library.The study found: Easy access to the King Abdulaziz Public Librarybecause of its average location in the city of Riyadh, as well as vertical expansionin the library building to accommodate future developments, the technologycurrently used in the library is fairly suitable, do not use the library systemsManagement of modern libraries.The most important recommendations are: to expedite the completion ofthe studies needed to develop the library's building and provide them with smartbuilding technology, and adopt a smart Libraries management systems: SLMs,developing library services and focusing on "information literacy " and "Continuous education ".This study is useful for decision makers responsible for the RiyadhInitiative Smart city where it reveals the role that the King Abdulaziz PublicLibrary can played in this initiative.